2004
DOI: 10.1590/s0004-282x2004000600002
|View full text |Cite
|
Sign up to set email alerts
|

Multi-minicore disease revisited

Abstract: -Multi-minicore disease (MmD) is an infrequent congenital myopathy, defined by structural changes in optic and electron microscopy, namely, multiple small areas lacking oxidative enzyme activity and focal disorganization of contractile proteins involving at most a few sarcomeres. The classical form of the disease manifests as more or less severe hypotonia and generalized weakness with predominance in axial and proximal limb muscles. Clinical variants also exist. Usually MmD is inherited as an autosomal recessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…3,4 Indeed, multi-minicore pathology can be found in other conditions, including muscular dystrophy, inflammatory myopathies, and endocrine myopathy, but additional pathologic changes are also found in those diseases. 5 Moreover, the obstetric history of respiratory insufficiency after general anesthesia for cesarean section in our patient was significant because it suggested that she might harbor a RYR1 mutation. The significant decremental response in RNST appears to be unique to our patients.…”
Section: Trapezius Abductor Digiti Minimni 5 MV 5 Msmentioning
confidence: 75%
“…3,4 Indeed, multi-minicore pathology can be found in other conditions, including muscular dystrophy, inflammatory myopathies, and endocrine myopathy, but additional pathologic changes are also found in those diseases. 5 Moreover, the obstetric history of respiratory insufficiency after general anesthesia for cesarean section in our patient was significant because it suggested that she might harbor a RYR1 mutation. The significant decremental response in RNST appears to be unique to our patients.…”
Section: Trapezius Abductor Digiti Minimni 5 MV 5 Msmentioning
confidence: 75%